Implementasi modul elektronik berpedekatan etnosains untuk meningkatkan kemampuan literasi sains peserta didik - Hidayati, Selvie Nur; Dewi, Novi Ratna (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2023)
Scientific literacy is an ability that students must have. Selection of the right module can improve scientific literacy skills. This study aims to analyze the effect and effectiveness of using electronic modules with an ethnoscience approach to increasing scientific literacy skills. The research used a quasi-experimental study with 64 research subjects in class VIII C as the experimental class and VIII D as the control class at SMP Negeri 1 Limbangan 2022/2023 academic year. Analysis of the effect of using electronic modules with an ethnoscience approach with the independent sample t-test formula on the posttest obtained tcount = 2.379> ttable (1.999) with sig(2-tailed) = 0.02 <0.05, so that there are differences in the test scores of the experimental class higher than the control class. The increase in scientific literacy skills after using an electronic module with an ethnoscience approach was analyzed using the N-Gain test in the experimental class, it was found that 0.396 was in the medium category and 0.217 in the control class was in the low category. So it can be concluded that the electronic module with an ethnoscience approach has an effect and can improve students' scientific literacy skills.